Evaluating Freshness Loss of Green Tea with Q10 Method and Weibull Hazard Analysis under Accelerated Shelf Life Testing - Mengxuan Xiao; Sitong Liu; Huozhu Jin; Mingji Xiao; Huiqiang Wang; Haiwei Zhang; Qianying Dai (Journal of Chemistry)
The important quality of green tea is freshness, but high temperature, light, oxygen, and humidity during storage may reduce the freshness of green tea. Thus, this study investigated the freshness loss of green tea (FLGT) under an accelerated shelf-life testing (ASLT) by sensory evaluation and acceptability test. The FLGTs of the samples stored at 20°C, 30°C, and 40°C, were determined as 67 days, 55 days, and 45 days, respectively by the Q10 method. In addition, they were further determined as 67 days, 57 days, and 42 days, respectively, by the Weibull Hazard Analysis (WHA). The sensory evaluation and acceptability test confirmed the correctness of the above results by 2-alternative choice analysis and chemical analysis. The Q10 method was applied to predict the FLGTs stored at 4°C and −20°C which were 93 days and 150 days, which was further verified by 2-alternative choice analysis and chemical analysis. The results show that it is possible to predict the suitable drinking period of green tea during storage by the Q10 method.